Case Study “Automaticity in L2 Learning and Teaching” Second Language Acquisition (Sla) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Our minds and bodies carry out many processes in our daily lives that take place automatically, without our control or even being aware of them. Moreover, this automaticity, which encompasses almost everything we do, is the subject of heated debate, and no consensus has yet been established on what automaticity is. The ambiguity of the definitions and the diversity of interpretations of the term automaticity make it difficult to define.